Building school capacity to support students from Australian Defence Force families during parental deployment. Issue 1 (April 2018) - Macdonald, Gail; Boon, Helen
Students who have parents deployed to a war zone are more vulnerable to an increased level of stress and anxiety, health problems, behavioural disorders and academic under-achievement. Yet, little is known about the processes employed by schools to support these students. This study investigated the deployment support work conducted by Defence School Transition Aides who are employed in some Australian schools to support students from Australian Defence Force families to manage the transitions associated with school mobility and parental absence for service reasons. Fifteen parents, 17 teachers and 15 Defence School Transition Aides were asked, in semi-structured interviews, to describe students' responses to parental deployment, how their schools supported students and what specific processes were employed by Defence School Transition Aides to assist students' coping during parental deployment. Findings from qualitative analyses, suggest that Defence School Transition Aides assist school communities to build their schools' capacity to support students with deployed parents by raising the school communities' awareness of these students' specific needs.